Corporate R&D intensity decomposition: Theoretical, empirical and policy issues - Pietro Moncada-Paternò-Castello (European Commission, Joint Research Centre (JRC), 2016)
Research and development (R&D) indicators are increasingly used not only to facilitate international comparisons, but also as targets for policies stimulating research. An example of such an indicator is R&D intensity. The decomposition method of R&D intensity was conceived with the aim of evaluating aggregate R&D intensity and explaining the differences in R&D intensity between countries. For policy purposes, it is particularly important to determine whether the differences are intrinsic (e.g. due to firmsâ exteuro™ underinvestment in R&D) or structural (e.g. due to differences in the sectors that make up an economy). Despite its importance for analytical purposes, the theoretical and methodological framework enabling decomposition of corporate R&D intensity has been elaborated only recently, and it is still not commonly used in the literature. Moreover, examination of the R&D intensity of firms in different industries and at different layers of aggregation leads to mixed results, the reasons for which are not fully understood. This paper aims to review the theoretical and methodological frameworks of corporate R&D intensity decomposition and how it is applied in the literature in order to determine the policy implications of empirical results that at first sight may seem to be contradictory. More specifically, this paper surveys the literature to determine (i) the theoretical framework of determinants of corporate R&D intensity, (ii) the methodologies that have been put in place to decompose corporate R&D intensity and the empirical results reached and (iii) the likely reasons for the contrasting results. Finally, the paper points out the possible policy implications and suggests some potential avenues for future research in this area.
Keywords: O30; O32; O38; O57; F23; R39; 330; corporate R&D intensity gap; decomposition; literature survey; R&D policy.